Controlled Synthesis of 2D Palladium Diselenide for Sensitive Photodetector Applications - Zeng, Long‐Hui; Wu, Di; Lin, Sheng‐Huang; Xie, Chao; Yuan, Hui‐Yu; Lu, Wei; Lau, Shu Ping; Chai, Yang; Luo, Lin‐Bao; Li, Zhong‐Jun; Tsang, Yuen Hong (Advanced functional materials, 2019)
Palladium diselenide (PdSe2), a thus far scarcely studied group‐10 transition metal dichalcogenide has exhibited promising potential in future optoelectronic and electronic devices due to unique structures and electrical properties. Here, the controllable synthesis of wafer‐scale and homogeneous 2D PdSe2 film is reported by a simple selenization approach. By choosing different thickness of precursor Pd layer, 2D PdSe2 with thickness of 1.2–20 nm can be readily synthesized. Interestingly, with the increase in thickness, obvious redshift in wavenumber is revealed by Raman spectroscopy. Moreover, in accordance with density functional theory (DFT) calculation, optical absorption and ultraviolet photoemission spectroscopy (UPS) analyses confirm that the PdSe2 exhibits an evolution from a semiconductor (monolayer) to semimetal (bulk). Further combination of the PdSe2 layer with Si leads to a highly sensitive, fast, and broadband photodetector with a high responsivity (300.2 mA W−1) and specific detectivity (≈1013 Jones). By decorating the device with black phosphorus quantum dots, the device performance can be further optimized. These results suggest the as‐selenized PdSe2 is a promising material for optoelectronic application. This study reports on the wafer‐area synthesis of a high‐quality 2D palladium diselenide (PdSe2) layer through a simple selenization method. Both experimental analysis and theoretical simulation reveal that the PdSe2 film exhibits a gradual transition from a semiconductor (monolayer) to semimetal (bulk). Further combination of PdSe2 with Si leads to a fast and sensitive broadband photodiode, with a high responsivity and specific detectivity.